A Cross-National Comparison of Intragenerational Variability in Social Media Sharing. (September 2020) - Mulvey, Michael S.; Lever, Michael W.; Elliot, Statia
Given Millennials' early digital life experiences, the adoption of social media tends to be greater among members of this generation compared to older ones. However, studies that report such age-based generalizations tend to neglect the phenomenon of intragenerational variability in social media use, providing an oversimplified picture of how people behave. Moreover, studies that compare social media use across nations are lacking, and are also needed to establish the generality of this phenomenon. This paper investigates intragenerational variability in social media sharing among Millennial travelers in six nations (Canada, France, India, Japan, Mexico, and USA) using Destination Canada's Global Tourism Watch database. A latent class segmentation model is used to identify groups of travelers with different ways of using social media to share trip experiences. Results supported five unique classes of social media sharing, ranging from nonuse to highly integrated sharing across many platforms. Additionally, class membership is predicted by covariates (nationality, travel experience, and social media use and goals) and is predictive of destination advocacy (offering recommendations). The identification of different classes of social media sharing advances theory on intragenerational and cross-national variability, and informs the development of international strategies that target Millennial travelers based on their tendency to share and advocate.